Efektivitas Penerapan Peraturan Walikota Palu No 34 Tahun 2023 Tentang Pencegahan dan Penanganan Perkawinan Usia Anak - Ridwan, Ridwan; Malarangan, Hilal; Yamani, Gasim (Lembaga Teewan Journal Solutions, 2026)
Child marriage is a serious social problem that requires structured regional intervention. This study aims to analyze the effectiveness of the implementation of Palu Mayor Regulation (Peraturan Walikota Palu) Number 34 of 2023 concerning the Prevention and Handling of Child Marriage, identify the supporting and inhibiting factors, and review the handling of its social impacts. This study uses a qualitative legal method with a descriptive-analytic approach, combining normative law and field research. Data were gathered through interviews with the Department of Women's Empowerment and Child Protection of Palu City and documentation from the Palu Religious High Court. The results indicate that the child marriage rate in Palu City remains fluctuating and significant, with 199 cases recorded between 2020 and 2024. While the legal substance of the regulation is comprehensive, its empirical implementation is not fully optimal. Effectiveness is constrained by limited budgetary resources, weak cross-sectoral institutional coordination, and deep-rooted cultural resistance within the community. Practically, it is recommended that the Government of Palu City strengthen policy implementation by increasing budget allocations, optimizing inter-agency collaboration frameworks, and engaging religious and community leaders to enhance public awareness.